Reinstating the marginalized body in nursing science: epistemological privilege and the lived life - McDonald, Carol; McIntyre, Marjorie (2001)
For nursing, the presence of bodies, the body of the patient and the body of the nurse are self-evident. Illness, pain and disability are essentially constituted as embodied experiences. Similarly, the nurse herself, in her body, is the primary and essential instrument of her practice. What is to be refuted, is the way in which the body is taken up in nursing discourse, the way in which the body of the patient and the body of the nurse are objectified, sanitized and stripped of embodied emotion and physicality. The authors propose that the ‘scientification’ of nursing limits what counts as nursing knowledge. This limitation undermines the central experience of nursing: the subjective and embodied experience of care. A number of factors contribute to the marginalization of the body and of embodied experience in nursing science. By privileging objective data and placing subjective experience outside the brackets of dominant scientific knowledge, practice disciplines such as nursing can become marginalized. To combat this marginalization, nursing and other professions have sought to situate themselves within the dominant frameworks. The result is that bodies are objectified, and person, practice, and embodied experience are subordinated to rational empirical intervention.
Keywords: Embodiment; feminist philosophy; lived life